Targeted pharmacologic immunomodulation for inborn errors of immunity. Issue 6 (20th August 2020) - Sacco, Keith A.; Stack, Michael; Notarangelo, Luigi D.
Abstract : Inborn errors of immunity consist of over 400 known single gene disorders that may manifest with infection susceptibility, autoimmunity, autoinflammation, hypersensitivity and cancer predisposition. Most patients are treated symptomatically with immunoglobulin replacement, prophylactic antimicrobials or broad immunosuppression pertaining to their disease phenotype. Other than haematopoietic stem cell transplantation, the aforementioned treatments do little to alter disease morbidity or mortality. Further, many patients may not be transplant candidates. In this review, we describe monogenic disorders affecting leucocyte migration, disorders of immune synapse formation and dysregulation of immune cell signal transduction. We highlight the use of off‐label small molecules and biologics mechanistically targeted to altered disease pathophysiology of such diseases.